Analisis Kesulitan Belajar Matematika Siswa Kelas 4 di SDN Bulak III Tangerang Selatan - Ina Magdalena; Hesty Tri Shafani; Vira Ramadhani (RC-INSTITUT, 2021)
The purpose of this study is to describe students' learning difficulties in Mathematics class 4 at SDN Bulak 3 in the 2020/2021 academic year and to describe the factors that cause difficulties in learning Mathematics in grade 4 at SDN Bulak 3 Academic Year 2020/2021. This study uses a descriptive research design. The subjects in this study were all 4th-grade students of SDN Bulak 3 which opened 40 students. Data collection techniques used in this study were interviews, questionnaires, and documentation. Data analysis uses an approach. The results of this study were 12 students who did not understand when the teacher delivered Mathematics material. The factors that cause difficulties in learning Mathematics for grade 4 students at SDN Bulak 3 are internal factors, namely students still have factors that are interested in participating in mathematics lessons, while externally, teachers do not use learning media as teaching aids and the methods used are less varied and innovative. Based on the results above, it can be seen that the 4th-grade students of SDN Bulak 3 still have difficulty in learning Mathematics.